Vaccination and Malaria Prevention among International Travelers Departing from Athens International Airport to African Destinations - Androula Pavli; Athina Spilioti; Paraskevi Smeti; Stavros Patrinos; Helena C. Maltezou (Journal of Tropical Medicine)
Background. International travel to Africa has grown dramatically over the last decade along with an increasing need to understand the health issues for travelers. The current survey aimed to assess vaccination and malaria prevention of travelers visiting Africa. Methods. A questionnaire-based survey was conducted from of November 1, 2011 to of April 30, 2013 at Athens International Airport. Results. A total of 360 travelers were studied; 68% were men. Their mean age was 39.9 years. Previous travel to tropical countries was reported by 71.9% of them. Most frequent destination was sub-Saharan Africa (60%). Most of them traveled for ≥1 month (62%). The main reason for travel was work (39.7%). Only 47% sought pretravel consultation. Hepatitis A, typhoid, and meningococcal vaccines were administered to 49.8%, 28%, and 26.6%, respectively, and malaria chemoprophylaxis to 66.8% of those who visited sub-Saharan Africa. A history of previous travel to a tropical country, elementary level of education, and traveling for visiting friends and relatives, and for short duration were significant determinants for not pursuing pretravel consultation. Conclusions. The current survey revealed important inadequacies in vaccine and malaria prophylaxis of travelers departing to Africa. Educational tools should be developed in order to improve awareness of travelers to risk destinations.